O diretor da Factory : a convergência de conceitos artísticos e publicitários na pintura de Andy Warhol entre 1960-68 - Scardini, Samir Torres Scardin (2016)
This study aimed to analyze part of the advertising and American painter Andy Warhol work and understand how to work the interrelationship of advertising fields and art in his works. Increase knowledge in the artist's work can contribute to creative innov